We Move Up Levels Together: Dignity, Transformative Marketing, and the Repurposing of Racial Capitalism - Ellison, Susan (Anthropologica, 2024)
Indigenous Bolivians, especially women, are climbing the ranks of global multilevel marketing (MLM) companies like Herbalife, Omnilife, and Hinode, seeking to join Bolivia’s purportedly rising Indigenous middle class. Through MLMs, Indigenous direct sales distributors pursue a dignified life materialized in better homes, smart dressing, international travel, and the respect they receive at recruitment events. In their recruitment and sales pitches to potential buyers and downline vendors, Indigenous distributors fashion testimonials about their successes that explicitly critique existing avenues of class mobility and their racialization in two ways. First, these testimonials counter the skepticism that multilevel marketing companies face by citing a litany of false promises offered by higher education, salaried employment, and public sector jobs—avenues long heralded as the stepping stones to entwined racial and class mobility in Bolivia. They further voice their frustrations with perceived status hierarchies and organizational barriers among Indigenous merchants, highlighting their own sense of alienation from the connections and protections that have enabled the financial success of other Indigenous entrepreneurs. Second, while lodging these critiques, distributors repurpose racialization toward their own recruitment ends. As MLM distributors pursue their visions of the good life, the testimonials that Indigenous MLM recruiters craft to enable their ascent expose, rely on, and rework the bounds of racial capitalism. Ultimately, their critiques reveal how the racial partitioning that enables capitalist extraction operates through the work of direct sales.